4(j-3)=2(j-7)

Apply the distributive property.

4j+4⋅-3=2(j-7)

Multiply 4 by -3.

4j-12=2(j-7)

4j-12=2(j-7)

Apply the distributive property.

4j-12=2j+2⋅-7

Multiply 2 by -7.

4j-12=2j-14

4j-12=2j-14

Subtract 2j from both sides of the equation.

4j-12-2j=-14

Subtract 2j from 4j.

2j-12=-14

2j-12=-14

Add 12 to both sides of the equation.

2j=-14+12

Add -14 and 12.

2j=-2

2j=-2

Divide each term in 2j=-2 by 2.

2j2=-22

Cancel the common factor of 2.

Cancel the common factor.

2j2=-22

Divide j by 1.

j=-22

j=-22

Divide -2 by 2.

j=-1

j=-1

Solve for j 4(j-3)=2(j-7)